2018
DOI: 10.1111/ijfs.13751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐pressure processing on immunoreactivity, microbial and physicochemical properties of hazelnut milk

Abstract: Summary This study investigated the effects of high‐pressure processing (HPP) and thermal processing (TP) on the overall quality attributes of hazelnut milk. HPP achieved the same microbial safety as TP, and the pH, °Brix and sugar contents were maintained at the levels of fresh hazelnut milk. Although HPP caused colour changes, the ∆E was smaller than that of the TP sample. Increasing pressure significantly decreased the immunoreactivity of the hazelnut milk by 70%, while simultaneously reducing the levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In almond milk, both TPC and TFC increased after PEF (28 kV/cm) treatment (Manzoor et al, 2020). Similar results were reported for bioactive compounds in hazelnut milk (Tsai et al, 2018) and fruit‐based soy milk (Morales‐de la Peña et al, 2010). It is generally thought that PEF‐induced alterations in the voltage‐gated ion channels lead to a rapid influx of Ca 2+ into the cell membrane thus increasing its permeability.…”
Section: Pulsed Electric Field Processingsupporting
confidence: 85%
See 2 more Smart Citations
“…In almond milk, both TPC and TFC increased after PEF (28 kV/cm) treatment (Manzoor et al, 2020). Similar results were reported for bioactive compounds in hazelnut milk (Tsai et al, 2018) and fruit‐based soy milk (Morales‐de la Peña et al, 2010). It is generally thought that PEF‐induced alterations in the voltage‐gated ion channels lead to a rapid influx of Ca 2+ into the cell membrane thus increasing its permeability.…”
Section: Pulsed Electric Field Processingsupporting
confidence: 85%
“…In addition to microbially safe and stable food products, HPP improves the functionality of various important bioactive compounds such as antioxidants which are normally lost with the application of heat (Tsai et al, 2018). Both anthocyanin and TPC increased in blueberry samples at first but eventually decreased during storage.…”
Section: Hig H -Pre Ssure Proce Ss Ingmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, it was observed that with a combination of high pressure and mild thermal treatment (75 • C), HPP altered the isoflavone profiles of soymilk through promoting a shift in the isoflavone profile from malonylglucosides toward β-glucosides [17]. Tsai et al [18] investigated the effects of HPP on the quality attributes of hazelnut milk during refrigerated storage, and found that HPP at 600 MPa for 5 min achieved the same level of microbial safety as thermal processing at 80 • C for 3 min and significantly decreased immunoreactivity without significantly changing the physicochemical properties of the hazelnut milk. In the present study, a pasteurization experiment was performed with HPP conditions that enabled a 5-log reduction of E. coli O157:H7, namely 200 MPa/240 s, 400 MPa/210 s, and 600 MPa/150 s. Results indicated that the inhibition of TAB, psychrotrophs, and E. coli/coliforms in HPP-treated samples were not significantly different compared to the HTST-treated samples up to 21 days of refrigerated storage.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great advances achieved during the last decades, HHP keeps being evaluated to assure safety in novel foods such as hazelnut milk [27], chokeberry juice [28], cucumber juice, mango nectar [29] and prickly pear juice [30]. Overall, HHP has the same efficacy as conventional pasteurization without modifying nutritional and sensory properties of the product.…”
Section: Basic Principles and Recent Applicationsmentioning
confidence: 99%